Design of a laser welding plugging system for the steam generators of high-temperature gas-cooled reactor. (May 2023) - Liu, Fuguang; Yang, Erjuan; Chen, Jipeng; Li, Yong; Mi, Zihao; Gong, Xinglong; Huang, He
Abstract: As fourth-generation nuclear power equipment, high-temperature gas-cooled reactor (HTGR) is attracting more and more attention both in industry and academia. The core outlet temperature of the steam generator (SG) in HTGR is much higher than that of pressurized water reactor steam generators, which is more likely to cause damage. Till now, welding plugging is still one of the important means to prevent the leakage of damaged heat transfer tubes. However, how to improve the automation of welding plugging to reduce the short-range operation time in a radioactive environment is still difficult. This work proposes the design of a laser welding plugging system for the HTGR. Firstly, the design requirements are analyzed and the overall design scheme is given. The whole system consists of a laser generator, a multi-axis robot, and supporting devices. Secondly, the key supporting devices including a laser welding head, a pneumatic clamping jaw, and a single-axis motion platform are explained in detail. The structure simulation based on SolidWorks is adopted, which provides the basis for the design of the single-axis motion platform. Thirdly, the control system which takes the PLC control system as the main control unit and the industrial computer as the monitoring data processing unit is described. Finally, an experimental system is built and the laser welding experiment is carried out to test the feasibility of the designed laser welding plugging system. Highlights: A novel laser welding plugging system is designed to improve the automation level of welding plugging. The plugging system is applicable to the narrow and long manhole structure in the steam generator. The width and depth of the weld proves the feasibility of the laser welding system.